A Literature review of research trends in the development of ethnoscience-based student worksheets in the field of science for the period 2020-2025 in Indonesia - Melia Astuti; Bambang Subali (Indonesian Journal of Science and Education, 2025)
This literature study aims to examine trends in research on the development of ethnoscience-based student worksheets through a literature study of relevant articles. Data collected from articles obtained through the PRISMA-based SLR method were analysed based on year of publication, university origin, education level, research model, learning model, ethnoscience context, and worksheet format. The results of the study show that the trend of research on the development of ethnoscience-based worksheets in the field of physics in the period 2020-2025 experienced a significant increase in 2024 with four articles published this year. Senior high school is the educational level that has been the focus of most research, while the ADDIE research development model is the most frequently used model (used in four articles). Interestingly, there is no dominant learning model associated with the development of ethnoscience-based worksheets in physics, which demonstrates the flexibility of the pedagogical approach. The most frequently used ethnoscience context is traditional musical instruments to explain sound wave material. In terms of worksheet format, development is still dominated by print formats (7 studies). In addition, the potential for exploring ethnoscience from various regions is still very large because no region dominantly explores ethnoscience in the reviewed physics worksheet development articles. The implications of this study highlight the need for further exploration at education levels other than senior high school, the development of digital worksheets, and the exploration of ethnoscience contexts from various regions to enrich physics learning that is more contextual and relevant to students.